Clostridium difficile infection in patients with inflammatory bowel disease - Czepiel, Jacek; Biesiada, Grażyna; Perucki, William; Mach, Tomasz (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Clostridium difficile is a bacterium widely distributed in the human environment. In the last decade the incidence and severity of Clostridium difficile infection has grown, particularly in Europe and North America, making it one of the more common nosocomial infections. A group particularly susceptible to Clostridium difficile infection are patients with inflammatory bowel disease, especially those with involvement of the colon. This paper presents relevant data on Clostridium difficile infections in inflammatory bowel disease patients, including epidemiology, pathogenesis, diagnosis and treatment.